Sistem Ekonomi Keluarga Nelayan di Desa Bulutui Kecamatan Likupang Barat Kabupaten Minahasa Utara - Kasim, Rahmat; Sambayang, Zahwa Fibrilia; Minabari, Sarah; Maku, Nathalia M Andini (Program Studi Sosiologi Agama Fakultas Ushuluddin, Adab dan Dakwah IAIN Manado, 2025)
This study aims to examine the economic system of fishing families in Bulutui Village, North Minahasa, emphasizing patterns of dependence on the sea and weather, work and profit-sharing systems, and the role of women in household economic activities. Bulutui Village was chosen as the research location because it represents a coastal community that still maintains a traditional economic structure based on social solidarity and local cultural values. This study used a qualitative approach. Data were collected through in-depth interviews, participant observation, and documentation with five key informants: fishermen, fish traders, catch collectors, and fishermen's wives. Data analysis was conducted thematically through the stages of domain, taxonomy, componential, and cultural theme identification. The results indicate that the economic system of fishing families in Bulutui is flexible and adaptive, heavily influenced by weather conditions and the fishing season. The profit-sharing system in fishing activities demonstrates a collective work structure based on trust and the contribution of roles, such as divers (mudung) and work groups (soma). Women play a central role in catch management, fish distribution, and micro-enterprises such as food cultivation and sales. The economic strategies developed by fishing families are not only survival-oriented but also demonstrate social resilience through cooperative networks and a community-based moral economy. These findings underscore the importance of recognizing local economic systems as part of inclusive and sustainable coastal development.